Generalized GNSS Signal Carrier Tracking: Part I—Modeling and Analysis - Yang, Rong (2017)
This paper presents a generalized theoretical framework for carrier tracking of global navigation satellite systems signals by constructing a state space representation for the carrier tracking loop and applying control system design techniques to derive state feedback and state estimator gain matrices. Both phase-locked loop and frequency-locked loop are studied using this approach. Their performances are evaluated using the closed-form expressions in the presence of thermal noise, oscillator noise, and receiver platform dynamics. The proposed approach unified the phase tracking and frequency tracking within the same theoretical framework, thereby facilitating a systematic analysis of the effects of tracking loop design parameters under weak signal and highly dynamic signal environments.